2001
DOI: 10.1002/ptr.815
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of some Moroccan medicinal plants

Abstract: The extracts of 12 plants selected on the basis of the folk-medicine reports were examined for their antibacterial effects against eight pathogenic bacteria. The n-butanol extract of Calotropis procera flowers and the aqueous extract of Eugenia caryophyllata proved to be the most effective against the bacteria tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 9 publications
2
27
0
3
Order By: Relevance
“…The previous study with C. procera has been shown that the plant has antibacterial and antiparasitic activities (Larhsini et al, 1999). Recently, Rahim et al (2016) studied the antimicrobial activity of methanol extract of A. ehrenbergiana which showed a wide spectrum activity against bacterial isolates but a poor inhibitory activity on fungi.…”
Section: Resultsmentioning
confidence: 99%
“…The previous study with C. procera has been shown that the plant has antibacterial and antiparasitic activities (Larhsini et al, 1999). Recently, Rahim et al (2016) studied the antimicrobial activity of methanol extract of A. ehrenbergiana which showed a wide spectrum activity against bacterial isolates but a poor inhibitory activity on fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts isolated from S. aromaticum are widely used and well known for their antibacterial and antifungal properties (Larhsini et al 2001;Ranasinghe et al 2002;Gayoso et al 2005). …”
Section: Resultsmentioning
confidence: 99%
“…Among them piperine is the major chemical constituent responsible for the bitter taste of the black pepper. It has been found that p. nigrum leaf extract inhibits the growth of bacterial strains (Larhsini et al, 2001;Sasidhran and Menon, 2010). According to the study not only the black pepper fruit part show the effectiveness but also every part show the effectiveness of numerous health related effects such as antibacterial, antifungal, and anticarcinogenic, antithrombicand vasodilator activities (Bidlack et al, 2000).…”
Section: Fig1 Effect Of Different Extracts On Bacterial Growthmentioning
confidence: 99%